Shear Performance Mechanism Description Using Digital Image Correlation. Issue 3 (3rd July 2018) - Strauss, Alfred; Castillo, Pablo; Bergmeister, Konrad; Krug, Bernhard; Wan-Wendner, Roman; Marcon, Marco; Matos, Jose; Casas, Joan Ramon
Abstract: In engineering, quality control in systems development ensures that products and services meet expectations. There is an increasing need to develop strategies to ensure asset quality and reduce the risk of unexpected costs. Ensuring the desired service quality with minimum interruptions requires maintenance actions when the risk of service impairment, interruption or losses in life-cycle costs reach predefined levels, which are based on performance indicators. This paper analyses a digital image correlation (DIC) system and its ability to assess performance indicators such as crack patterns, crack openings and vertical and horizontal deformation. The obtained values are then compared to goals so that structural performance assessment strategies can be implemented in an efficient and sustainable way. In particular, the system is used to obtain valuable information about the shear transfer mechanisms of reinforced concrete beams. This contribution focuses on prestressed precast beams loaded in shear following a sequence of loading and unloading cycles before the load is ultimately increased until failure. The obtained results include a load-dependent photogrammetric documentation of crack patterns, a continuous quantification of crack openings and an accurate measurement of vertical and horizontal deformation. These findings are basic elements for the enhancement and assessment of existing analytical formulations.